EFFECTS OF WATER STRESS ON GROWTH, OIL YIELD, FATTY ACID COMPOSITION AND MINERAL CONTENT OF SESAMUM INDICUM - A. Ozkan; M. Kulak (Journal of Animal and Plant Sciences, 2013)
Effects of water deficit on herbal growth, oil yield, fatty acid composition and mineral content in Sesamum indicum L. (Cultivars Cumhuriyet and Özberk) aerial and edible parts were investigated in greenhouse conditions in 2012. Plants were subjected to the different levels of water deficiency; control (FC, Field Capacity), moderate water deficit (1/2 of FC) and severe water deficit (1/4 of FC). The experiments were arranged as a factorial, using a randomized complete design with three replications. Plant growth parameters were significantly reduced by 1/4 FC and consequently caused reductions in seed yield and yield parameters. Drought did not influence the oil yield. With the increasing water deficit treatments, oleic acid content of both cultivars decreased but it was more pronounced for cv. Cumhuriyet. However, linoleic acid percentage of cv. Cumhuriyet was not influenced with the decreasing field capacity whereas it was positively affected with the treatment for cv. Özberk. Minor fatty acid compounds such as arachidic acid, linolenic acid, lignoceric acid, and behenic acid were not statistically affected for both cultivars when exposed to different level of treatment except cis-11-eicosenoic acid. Besides, mineral contents (Ca, Mg, K, Na) showed variation depending on cultivars and water deficit treatments except Na content.
Keywords: Sesame; water deficit; fatty acid; mineral content; plant growth